Sharia insurance efficiency in Indonesia and Malaysia using the stochastic frontier approach analysis - Zubaidah Nasution (Asian Journal of Islamic Management (AJIM), 2021)
Purpose: This study aims to analyze the efficiency level of Indonesian sharia insurance and Malaysian takaful with a parametric stochastic frontier approach where the input is total assets and expenses, and the output of this research is claims and premiums.Methodology: This study uses quantitative methods with secondary data in the form of shariah insurance Malaysia and Indonesia annual reports 2016-2020. The data analysis uses a regression test with the help of stochastic frontier approach (SFA)Findings: Based on the results of processing using stochastic frontier analysis (SFA), Indonesian Sharia insurance's overall production efficiency level is known to be 0.6306 or 63.06%, Malaysian takaful on average is known to be 0.6160 or 61.60 %. Partially, Indonesian sharia insurance total assets, insurance expenses, and claims positively and significantly affect the number of premiums. Takaful Malaysia's total assets of Malaysian takaful partially have an insignificant negative effect on the premium amount. Malaysia's takaful expenses and claims partially have an insignificant positive effect on the premium amount.Originality: This study analyzes the efficiency and looks at the effect of the variables of Indonesian sharia insurance and Malaysian takaful with a parametric stochastic frontier approach.Practical implications: This research shows that the management of Indonesian sharia insurance and Malaysia's takaful is still inefficient, so each government needs to regulate the operations in this industry.